A Study of Consumer Behaviour on Purchase Intention towards McDonald’s in Malaysia - Chen Shi Min (International Journal of Applied Business and International Management, 2022)
McDonald's has more than 36,000 restaurants worldwide and also is the world's leading quick service restaurant chain. In the international fast-food business, McDonald's has a strong vision of providing the finest fast-service eating experience. The objective of this research is to survey determinants which affect consumer behaviour on purchase intention towards McDonald’s in Malaysia. We would like to do a survey whether service quality, pricing, product quality and location preference are determinants of affecting consumer behaviour on purchase intention toward McDonald’s. Various sources including an online survey were used to obtain the primary and secondary data for this investigation. A total of 150 loyal customers of McDonald's will participate in the online survey via Google Forms. We tested the hypothesis using SPSS software. This study indicated that service quality, pricing, product quality and location preferences are significant determinants of affecting purchase intention towards McDonald’s. This research provides new insights, and recommendations are presented.  Keywords: Location preferences, Purchase intention, Pricing, Product Quality, Service Quality